Immunity: Psoriasis comorbid with atherosclerosis - Liu, Chunping; Chen, Huiqi; Liu, Yanjiao; Huang, Haiding; Yu, Wanling; Du, Tingting; Long, Xinyao; Chen, Xinming; Chen, Zhijun; Guo, Sien; Li, Jinxin; Jiang, Zebo; et al. (Frontiers in Immunology, 2022)
Psoriasis is an immune-mediated, persistent inflammatory disease with a genetic predisposition, and the involvement of multiple organs in psoriasis remains indicative of systemic disease. Atherosclerosis (AS) is a common complication of patients with severe or prolonged psoriasis. The specific pathogenesis of psoriasis is still unclear. Current studies suggest that psoriasis is a polygenic genetic disease with the interaction of multiple factors such as heredity and environment. Keratinocytes are proliferated through immune-mediated inflammatory pathway, which leads to cell activation, infiltration of dermis cells and release of inflammatory factors. Activation of inflammatory cells and pro-inflammatory factors play an important role in the progression of psoriasis and atherosclerosis. Studies have found that there is a close relationship between psoriasis and atherosclerosis, and systemic inflammation may be the common feature of psoriasis and AS. This paper attempts to explore the possibility of the relationship between psoriasis and atherosclerotic comorbidities from the aspects of potential epidemiology and immune mechanism, in order to provide some reference for the subsequent scientific research.